2019
DOI: 10.1007/s11104-019-04342-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal utilization of different phosphorus sources in a glacier forefront in the Italian Alps

Abstract: AimsIn deglaciated surfaces, lithology influences habitat development. In particular, serpentinite inhibits soil evolution and plant colonization because of insufficient phosphorus (P) content, among other stressful properties. In nutrient-poor environments, ectomycorrhizal fungi (EMF) play a key role exploring the soil for P beyond the rhizosphere. In this study, we followed the role of EMF in accessing inorganic and organic P along two proglacial soil chronosequences in the Alps (NW Italy), respectively char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
8
1
Order By: Relevance
“…These results indicated that regardless of the type of mineral and its sorption strength and stability toward OP, plants are able to take up at least a small portion of it for their nutrition. This agree with laboratory and greenhouse studies indicating that speci cally adsorbed P was potentially available to plants although it was very di cult to desorb (Bollyn et al, 2017;D'Amico et al, 2020;He et al, 1994;Martin et al, 2002;Montalvo et al, 2015;Par tt, 1979;Shang et al, 1996). Thus, even under conditions where the activities of plant microbiomes and roots that can help mobilize P are limited, OP-mineral complexes still have potential for supplying P to plants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results indicated that regardless of the type of mineral and its sorption strength and stability toward OP, plants are able to take up at least a small portion of it for their nutrition. This agree with laboratory and greenhouse studies indicating that speci cally adsorbed P was potentially available to plants although it was very di cult to desorb (Bollyn et al, 2017;D'Amico et al, 2020;He et al, 1994;Martin et al, 2002;Montalvo et al, 2015;Par tt, 1979;Shang et al, 1996). Thus, even under conditions where the activities of plant microbiomes and roots that can help mobilize P are limited, OP-mineral complexes still have potential for supplying P to plants.…”
Section: Discussionsupporting
confidence: 87%
“…There is also some experimental evidence that most of the P taken up by plants originates from the soil mineral-OP complex, although adsorbed OP is not easily or widely desorbed (Ahmed et al, 2021;He et al, 1994). This implies that OP associated with soil minerals is potentially available to plants, although its availability also depends on the type of soil minerals and the OP compound (Andrino et al, 2019;D'Amico et al, 2020). Recently, D'Amico et al (2020) exposed mesh bags lled with goethite associated with IP or IHP for 13 months to P-de cient soils in the Italian Alps.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also differ from those of Parfitt (1979); Andrino et al (2019), andD'Amico et al (2020), who showed that P associated with goethite was at least partly bioavailable in studies using soil or solid substrates instead of nutrient solutions. In the study of Andrino et al (2019), arbuscular mycorrhiza associated with tomato plants were able to acquire goethiteassociated P. On the one hand, this finding might differ from our results because different types of plants and mycorrhiza were studied.…”
Section: Phosphorus From Lüss Subsoil and From The Added Adsorption Complexes Is Not Available To Beechcontrasting
confidence: 99%
“…As described in section "Phosphorus From Lüss Subsoil and From the Added Adsorption Complexes Is Not Available to Beech, " organic P adsorbed to goethite was shown to be less available than adsorbed inorganic P in other studies (Andrino et al, 2019;Klotzbücher et al, 2019;D'Amico et al, 2020). This was probably caused by slower desorption of organic P than of inorganic P in the study of D'Amico et al (2020), in which mycorrhizal colonization of the goethite-P-complexes was measured, and in the study of Klotzbücher et al (2019), in which desorption induced by a chemical gradient was determined. Desorption rates for organic P from goethite might have been lower than those for inorganic P because of stronger bindings of organic P than of inorganic P to goethite.…”
Section: Phosphorus From Lüss Subsoil and From The Added Adsorption Complexes Is Not Available To Beechmentioning
confidence: 91%
See 1 more Smart Citation